2021
DOI: 10.3390/foods10112761
|View full text |Cite
|
Sign up to set email alerts
|

A Physiological-Based Model for Simulating the Bioavailability and Kinetics of Sulforaphane from Broccoli Products

Abstract: There are no known physiological-based digestion models that depict glucoraphanin (GR) to sulforaphane (SR) conversion and subsequent absorption. The aim of this research was to make a physiological-based digestion model that includes SR formation, both by endogenous myrosinase and gut bacterial enzymes, and to simulate the SR bioavailability. An 18-compartment model (mouth, two stomach, seven small intestine, seven large intestine, and blood compartments) describing transit, reactions and absorption was made.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…They reduced DOX-mediated cardiotoxicity in animal models and appeared to be safe and tolerable in human trials. Unfortunately, curcumin and EGCG have a low bioavailability, ranging between 1 and 2% of the orally administered dose [ 208 , 211 ], whereas sulforaphane is present in serum at 10–63% after oral intake [ 213 ]. A phase II trial with curcumin (2 g/d, oral) and a FOLFOX regimen showed no differences in quality of life (QOL) or neurotoxicity [ 177 ].…”
Section: Discussionmentioning
confidence: 99%
“…They reduced DOX-mediated cardiotoxicity in animal models and appeared to be safe and tolerable in human trials. Unfortunately, curcumin and EGCG have a low bioavailability, ranging between 1 and 2% of the orally administered dose [ 208 , 211 ], whereas sulforaphane is present in serum at 10–63% after oral intake [ 213 ]. A phase II trial with curcumin (2 g/d, oral) and a FOLFOX regimen showed no differences in quality of life (QOL) or neurotoxicity [ 177 ].…”
Section: Discussionmentioning
confidence: 99%
“…GLSs and the enzyme MYR are stored in different compartments of plant cells, requiring plant tissue to be damaged for cellular breakdown to occur and MYR to be released and act on GLSs. Therefore, the processing of cruciferous vegetables (i.e., by mastication, cutting, chopping) has an important impact on the bioavailability of GLSs and their hydrolysis products [ 139 , 140 ]. Furthermore, MYR tends to be denatured when cooking cruciferous vegetables, particularly in conditions of increased temperature (>80 °C) and prolonged cooking [ 136 ].…”
Section: Nutraceuticalsmentioning
confidence: 99%
“…In plant cells, GLS are physically separated from myrosinases and come in contact only upon tissue damage or crushing. Importantly, myrosinase is not expressed by mammalian cells; however, a small proportion is converted in the mouth by action of plant myrosinase released by chewing ( 76 ); moreover, the gut microbiota is entailed with myrosinase activity and constitutes the major site in humans where GLS are hydrolyzes to ITCs ( 77 ). While GLS are chemically stable and are characterized by a relatively long half-life, ITCs are highly reactive and short-lived in vivo ( 75 , 78 ).…”
Section: Dietary Sources and Chemical Nature Of Oscsmentioning
confidence: 99%